Corporate rebranding design of oil and gas company in Malaysia: case study of SMART Petrol / Amina Syarfina Abu Bakar...[et.al] - Abu Bakar, Amina Syarfina; Harun, Azahar; Abd Razak, Mohamed Razeef (2016)
The aim of this study is to investigate the existing branding design and the potential of corporate rebranding design for SMART Petrol. SMART Petrol is a 100% Bumiputera companies that are actively involved in the supply and marketing of petroleum products in Malaysia. This company has been approved by the government to develop and modernize and supply of petroleum to gas station mini in rural areas. However SMART Petrol is new and unrecognized petrol station company in Malaysia, this caused lack of consumer’s trust and awareness. Through visual observation and content analysis of existing branding design, these could help restructuring process and trigger a new strategy of branding for SMART Petrol. Social responsibilities seem significant to get closer to the consumers. Due to that corporate rebranding design is important to gain the consumer’s trust and new shareholders to invest to with SMART Petrol for potential booster of the company. Therefore the decision of rebranding for failure organization is important and seems rational.